VD_FINDINFO Jug / 2015 / 437 vom 11. März 2015 - VD Tribunal cantonal (2015)
VENTE D'IMMEUBLE, GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE, DROIT À LA RÉSOLUTION DU CONTRAT | 197 CO, 200 CO, 205 CO, 208 CO, 221 CO